ANALISIS KEPUASAN KEPALA SEKOLAH TERHADAP ALUMNI PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH DI DAERAH MINORITAS ISLAM - Komayanti; Hikmah, Afroh Nailil; Chudzaifah, Ibnu (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
The aim of this research is to analyze the level of satisfaction of school principals towards alumni of the PGMI Study Program in Islamic minority areas, namely in Sorong City. The principal's satisfaction with alumni's performance in the field can provide an important picture regarding the relevance and quality of education provided by the study program. Through a quantitative approach, data will be collected from school principals in Sorong City through questionnaires and interviews. Data will be analyzed to identify factors that influence principal satisfaction and its impact on the study program. It is hoped that the findings of this research can provide valuable input for curriculum development, learning strategies, and improving the quality of graduates in the context of Islamic minority areas.